Postsurgical Care for Rehabilitation With Implant-Retained Extraoral Prostheses - Goiato, Marcelo Coelho [UNESP]; Takamiya, Aline Satie; Negrao Alves, Luciana Mara; Santos, Daniela Micheline dos [UNESP] (Lippincott Williams & Wilkins, 2010)
The health of a peri-implant tissue is a critical factor for the long-term success of treatment with extraoral implants. However, infection and inflammation may occur and lead to implant loss and prostheses failure. Therefore, some postsurgical care as hygiene with soap and water, soft toothbrush, and Superfloss type dental floss and medication with anti-inflammatory and antibiotic are suggested to avoid complications. In addition, a thin and smooth layer of subcutaneous tissue in the peri-implant area should be preserved during implant insertion to favor the assistance recommended in this phase.
Keywords: Extraoral implant; maxillofacial prosthesis; postsurgical care